The Hfq regulon of Neisseria meningitidis. Issue 6 (25th April 2017) - Huis in 't Veld, Robert A. G.; Kramer, Gertjan; van der Ende, Arie; Speijer, Dave; Pannekoek, Yvonne
Abstract : Neisseria meningitidis causes septicemia and bacterial meningitis leading to significant morbidity and mortality worldwide. Its remarkable ability to change from colonizing the nasopharynx to invading the bloodstream and CSF requires quick adaptations of its cellular composition. In this study, we used high‐resolution quantitative proteomic analyses to further elucidate the role of the chaperone protein Hfq in these adaptations. Abstract : The conserved RNA‐binding protein, Hfq, has multiple regulatory roles within the prokaryotic cell, including promoting stable duplex formation between small RNAs and mRNAs, and thus hfq deletion mutants have pleiotropic phenotypes. Previous proteome and transcriptome studies of Neisseria meningitidis have generated limited insight into differential gene expression due to Hfq loss. In this study, reversed‐phase liquid chromatography combined with data‐independent alternate scanning mass spectrometry (LC‐MS E ) was utilized for rapid high‐resolution quantitative proteomic analysis to further elucidate the differentially expressed proteome of a meningococcal hfq deletion mutant. Whole‐cell lysates of N. meningitidis serogroup B H44/76 wild‐type (wt) and H44/76Δ hfq (Δ hfq ) grown in liquid growth medium were subjected to tryptic digestion. The resulting peptide mixtures were separated by liquid chromatography (LC) prior to analysis by mass spectrometry (MS E ). Differential expression was analyzed by Student's t ‐test with control for false discovery rate (FDR). Reliable quantitation of relative expression comparing wt and Δ hfq was achieved with 506 proteins (20%). Upon FDR control at q  ≤   0.05, 48 up‐ and 59 downregulated proteins were identified. From these, 81 were identified as novel Hfq‐regulated candidates, while 15 proteins were previously found by SDS/PAGE/MS and 24 with microarray analyses. Thus, using LC‐MS E we have expanded the repertoire of Hfq‐regulated proteins. In conjunction with previous studies, a comprehensive network of Hfq‐regulated proteins was constructed and differentially expressed proteins were found to be involved in a large variety of cellular processes. The results and comparisons with other gram‐negative model systems, suggest still unidentified sRNA analogs in N. meningitidis .